(untitled) (Journal of Social Sciences Review, 2023)
The Sino-US relationship has seen many drawbacks and triumphs over the years. Today they both are struggling to legitimize their rule and capabilities while also contesting and, at times, defying one another. Afterwards, the conclusion of the Cold War, a general sense of amusement ran over policymakers in the United States, and western scholars started to debate over the “End of History” and celebrated the glories of “liberal democratic order” however, the revival of the Chinese diplomacy brought back novel fears of the advent of a New Cold War, this time between the Cold War allies. This paper aims to explore the Sino-US Cold War, particularly at the heart of the Indo-Pacific at the South China Sea. The highly disputed waters of the South China Sea are proving a testing ground for both China and the United States. Furthermore, the relevance of the United Nations Convention on the law of the Sea (UNCLOS) and its alleged violation by China is also the focus of this paper. Defying the United States in the South China Sea as well as forging a business partnership with the US, will be much more challenging for China. This qualitative research explores the start of the New Cold War and how it might escalate into a never-ending battle of power and dominion.